Pengaruh Kinerja Keuangan terhadap The Corporate Value Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) - Maria Junianta (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2022)
This study aims to analyze the influence of Current Ratio and Return On Assets towards Price to Book value. The data analysis models used in this study are descriptive and inference statistical analysis. The population in this study is mining sector listed on the Indonesia Stock Exchange during the period of 2013 to 2017. The sample is chosen by using purposive sampling 33 companies are chosen since they have fulfiled the criteria, that is having annual financial reports during the study period 2013-2017. The result shows that the variables Current Ratio have significant negative effect on corporate value. The result also shows that the variables Return On Assets have a significant positive effect on corporate value.